2014
DOI: 10.1007/s10257-014-0245-4
|View full text |Cite
|
Sign up to set email alerts
|

A visual analysis of the process of process modeling

Abstract: Abstract. The construction of business process models has become an important requisite in the analysis and optimization of processes. The success of the analysis and optimization efforts heavily depends on the quality of the models. Therefore, a research domain emerged that studies the process of process modeling. This paper contributes to this research by presenting a way of visualizing the different steps a modeler undertakes to construct a process model, in a so-called PPMChart. The graphical representatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…Their analysis shows that most approaches use the modeling results as their objects of investigation and omit the process of modeling itself. This diagnosis remains true also in more recent research (Nelson et al 2011;Claes et al 2013). In this light, Gemino and Wand (2004) propose to also to assess the effectiveness of the process of model creation and model interpretation.…”
Section: Related Workmentioning
confidence: 81%
See 1 more Smart Citation
“…Their analysis shows that most approaches use the modeling results as their objects of investigation and omit the process of modeling itself. This diagnosis remains true also in more recent research (Nelson et al 2011;Claes et al 2013). In this light, Gemino and Wand (2004) propose to also to assess the effectiveness of the process of model creation and model interpretation.…”
Section: Related Workmentioning
confidence: 81%
“…Examining the process of conceptual modeling is an area of research that has gained momentum in the last years (Claes et al 2013;Soffer et al 2012). Research in the area of process management traditionally has taken the existence of appropriate models for granted (Hjalmarsson et al 2015), and has hardly addressed the questions of how models should be created, who should be involved during creation, and how an appropriate representation of the real world could be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Sedrakyan, et al performed a process mining analysis on observational data and concluded that process modeling seems to require more effort than data modeling, and that in general it seems to be a successful tactic to start with the essence and iteratively add details to your model, which results in a quick growth of the model at the start and a slower pace of adding elements later on when thinking about the more challenging details [21]. To conclude, Claes, et al described various patterns of process modeling, ranging from timing and spread of creation, movement and deletion of model elements to more general modeling patterns such as the process modeling styles discussed in Section 3.1 [9,11].…”
Section: 2mentioning
confidence: 99%
“…This approach consists of three phases. First, a set of more than 1.000 observations of modeling sessions was collected and analyzed [8,9]. Second, we are currently completing the knowledge generation phase guided by the work of Gregor, et al about theory building [10].…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of creating BP models, some works focus on investigating the way a process modeler creates a process model and link the implemented modeling approach to the syntactic and semantic quality and the understandability of the resulting model (e.g., [4], [15]). One of the main conclusions from these works is that modelers have various styles of modeling and that a structured approach (i.e.…”
Section: Related Workmentioning
confidence: 99%